Focal adhesion kinase as a new player in the biology of onco-hematological diseases: the starting evidence - Capasso, Guido; Mouawad, Nayla; Castronuovo, Maria; Ruggeri, Edoardo; Visentin, Andrea; Trentin, Livio; Frezzato, Federica (Frontiers in Oncology, 2024)
Focal Adhesion Kinase (FAK) is a non-receptor tyrosine kinase mainly found in the focal adhesion regions of the plasma membrane and it has a crucial role in migration and re-modelling of cellular morphology. FAK is also linked to several aspects of cancer biology, from cytokines production to angiogenesis, drug resistance, invasion and metastasis, as well as epithelial-to-mesenchymal transition. The gene locus of FAK results frequently amplified in several human tumors, thus causing a FAK overexpression in several cancers. Furthermore, FAK is able to influence extracellular matrix production and exosomes secretion by cancer-associated fibroblasts, thus having an important role in tumor microenvironment regulation. While on the one hand the role of FAK in solid tumors is well known, on the other hand its importance in onco-hematological diseases remains poorly explored. This review collects studies related to FAK significance in onco-hematological diseases and their microenvironments. Overall, FAK importance in blood tumors is increasingly evident, but further research is required to confirm FAK as a new therapeutic target in the hematological contexts.